Progressive primary education in a South African homeland : a review of Breakthrough to Literacy in Bophuthatswana - Makhele, Enos Moeti (The University of Edinburgh, 1987)
The introduction of adapted versions of the British reading scheme Breakthrough to Literacy in South Africa and her "independent" homelands is significant in several ways. Firstly, it refocuses our attention on black education language policy in this region. Secondly, it raises questions about the innovative strength of such a scheme in an area which was not necessarily in the minds of its designers. Language and language policy have been both political and educational issues in South Africa. Some of the most important political decisions made by the South African government have had language as their underlying factor. A good example is the present homeland policy of this government. The division of black people and their assignment to differing homelands has been based on their linguistic affiliation. It is therefore common to come across people who believe that the South African government would welcome any effort aimed at improving the status of black languages. This is because of the insistence of the South African government on the recognition and promotion of black languages as being both culturally and educationally important. The introduction of the Breakthrough reading scheme and the subsequent reaction of the education authorities in South Africa clearly belie this belief. (ii) To demonstrate this point, this study looks at the application and effects the scheme has had in one of the South African homelands. It also shows how its introduction coincided with the need to improve primary school education in these homelands. And why the scheme has not been officially recognised and supported by education authorities in South Africa itself despite its unofficial existence in black schools in the townships.
Keywords: Breakthrough to Literacy; Literacy; Education, Elementary; Progressive education